Guayaquil consensus: financial neutrality in organ donation (2025)
In the context of projections for Latin America, the Guayaquil Document is expected to serve as a crucial reference framework for establishing policies that ensure financial neutrality in the region. As we move towards 2030, countries in the area will likely adopt stricter measures to ensure donors do not incur economic losses from their altruistic decisions. Considering the recent legislative proposal from the United States—the End Kidney Deaths Act (H.R. 9275, 118th Congress)—which proposes a $50,000 tax deduction for living kidney donors ($10,000 annually for five years), the signing societies express their deep ethical, legal, and social concerns. Although the project states its purpose of reducing mortality from chronic kidney disease (CKD), its implementation sets a precedent that contradicts the universal principles of altruistic donation and financial neutrality enshrined in the Istanbul Declaration (2018) and the WHO Guiding Principles (2010). This document alerts health authorities, legislators, ethics committees, medical societies, and international organizations in Latin America and the Caribbean to the risks that such initiatives may pose to more fragile systems, eroding public trust and compromising distributive justice and human dignity. This document has been consensually agreed upon and approved by all nephrology societies in Latin America that comprise SLANH during the XXI Congress of SLANH, held in Guayaquil, Ecuador, from August 27 to 30, 2025. It has also been subscribed, discussed, consensually agreed upon, and approved by the transplant societies of Latin America and the Caribbean that form STALYC during the XXVI Latin American and Caribbean Transplant Congress and the V Paraguayan Transplant Congress, held in Asunción, Paraguay, from October 1 to 3, 2025.